First-in-Human Robot-Assisted Subretinal Drug Delivery Under Local Anesthesia - Cehajic-Kapetanovic, Jasmina; Xue, Kanmin; Edwards, Thomas L.; Meenink, Thijs C.; Beelen, Maarten J.; Naus, Gerrit J.; de Smet, Marc D.; MacLaren, Robert E. (American journal of ophthalmology, 2022)
To report the results of a first-in-human study using a robotic device to assist subretinal drug delivery in patients undergoing vitreoretinal surgery for macular hemorrhage. Double-armed, randomized controlled surgical trial (ClinicalTrials.gov identifier: NCT03052881). The study was performed at the Oxford Eye Hospital, Oxford University Hospitals NHS Foundation Trust, Oxford, United Kingdom. In total, 12 participants were recruited—6 in the robot-assisted and 6 in the control manual surgery arm according to the prespecified inclusion and exclusion criteria. All subjects presented with acute loss of vision owing to a subfoveal hemorrhage secondary to neovascular age-related macular degeneration. After standard vitrectomy, intraoperative optical coherence tomography–guided subretinal injection of tissue plasminogen activator (TPA) was performed by either robot-assisted or conventional manual technique under local anesthesia. The robotic part of the procedure involved advancement of a cannula through the retina and stabilizing it during foot-controlled injection of up to 100 µL of TPA solution. We assessed surgical success, duration of surgery, adverse events, and tolerability of surgery under local anesthesia. The procedure was well tolerated by all participants and safely performed in all cases. Total duration of surgery, time taken to complete the injection, and retinal microtrauma were similar between the groups and not clinically significant. Subretinal hemorrhage was successfully displaced at 1 month postintervention, except for 1 control subject, and the median gain in visual acuity was similar in both arms. This first-in-human study demonstrates the feasibility and safety of high-precision robot-assisted subretinal drug delivery as part of the surgical management of submacular hemorrhage, simulating its potential future application in gene or cell therapy.